Functional MRI Evaluation of Multiple Neural Networks Underlying Auditory Verbal Hallucinations in Schizophrenia Spectrum Disorders - Thoma, Robert. J.; Chaze, Charlotte; Lewine, Jeffrey David; Calhoun, Vince D.; Clark, Vincent P.; Bustillo, Juan; Houck, Jon; Ford, Judith; Bigelow, Rose; Wilhelmi, Corbin; Stephen, Julia M.; Turner, Jessica A. (Frontiers in Psychiatry, 2016)
Functional MRI studies have identified a distributed set of brain activations to be associated with auditory verbal hallucinations (AVH). However, very little is known about how activated brain regions may be linked together into AVH-generating networks. Fifteen volunteers with schizophrenia or schizoaffective disorder pressed buttons to indicate on-set and off-set of AVH during fMRI scanning. When a general linear model (GLM) was used to compare BOLD signals during periods in which subjects indicated that they were versus were not experiencing AVH (‘AVH-on’ versus ‘AVH-off’), it revealed AVH-related activity in bilateral inferior frontal and superior temporal regions; the right middle temporal gyrus; and the left insula, supramarginal gyrus, inferior parietal lobule and extra-nuclear white matter. In an effort to identify AVH-related networks, the raw data were also processed using independent component analyses (ICA). Four ICA components were spatially consistent with an a priori network framework based upon published meta-analyses of imaging correlates of AVH. Of these four components, only a network involving bilateral auditory cortices and posterior receptive language areas was significantly and positively correlated with the pattern of AVH-on versus AVH-off. The ICA also identified two additional networks (occipital-temporal and medial pre-frontal), not fully matching the meta-analysis framework, but nevertheless containing nodes reported as active in some studies of AVH. Both networks showed significant AVH-related profiles, but both were most active during AVH-off periods. Overall, the data suggest that AVH generation requires specific and selective activation of auditory cortical and posterior language regions, perhaps coupled to a release of indirect influence by occipital and medial frontal structures.